The importance of sensory-motor control in providing core stability: Implications for measurement and training - Borghuis, J.; Hof, A. L.; Lemmink, K. A. P. M. (Sports Medicine, 2008)
Although the hip musculature is found to be very important in connecting the core to the lower extremities and in transferring forces from and to the core, it is proposed to leave the hip musculature out of consideration when talking about the concept of core stability. A low level of co-contraction of the trunk muscles is important for core stability. It provides a level of stiffness, which gives sufficient stability against minor perturbations. Next to this stiffness, direction-specific muscle reflex responses are also important in providing core stability, particularly when encountering sudden perturbations.